Implementation of the Sustainable Development Goals as an opportunity for greater socio-economic integration within the European Union - Emilia Kiabukazi Bamwenda; Richard Girling (The Central European Review of Economics and Management (CEREM), 2018)
Aim: The aim of this article is to discuss the global and European concepts of sustainable development and how they can enhance European integration.Design / Research methods: The analysis of statistical data will show positive and negative trends in Europe. In addition, barriers to the implementation of the sustainable development strategy will be indicated, as well as areas in which the EU should put more effort into achieving its ambitious goals.Conclusions / findings: European Union countries stand out in the international arena for their high standard of living, made possible by a high level of economic development and extensive social welfare systems. However, at the turn of the 20th and 21st centuries it became clear that maintaining these high standards in the face of fundamental changes - both externally and internally - would require a significant reorientation of the current development policy. Euroscepticism, European integration, globalization and the increasing competitiveness of the rapidly growing Indian and Chinese economies, the IT revolution, the rise of the importance of knowledge and innovation, the prospect of depleting non-renewable natural resources crucial for modern development (combined with the associated risk in prices) are all becoming increasingly prominent in the list of challenges which Europe faces.Originality / value of the article: The article discusses the current statistical data of the whole concept of sustainable development rooted in the Europe 2020 program in contrast to other, studies, which in the majority focus on one issue of European programs.Implications of the research: This analysis complements the discourse regarding the Europe 2020 strategy.Key words: Sustainable Development, European Union, European initiatives, integration, GDP.JEL: Q01, F15
Keywords: Q01; F15; 330; Sustainable Development; European Union; European initiatives; integration; GDP